Multi-Link Leisure Developments Ltd v North Lanarkshire Council: Commercial Interpretation or Relief From a Bad Bargain? - Taylor, AdÃ¨le (Victoria University of Wellington Law Review, 2012)
In the 2011 decision Multi-Link Leisure Developments Ltd v North Lanarkshire Council, the United Kingdom Supreme Court purported to apply a business common sense approach to the interpretation of an option clause in a lease. In particular, several of the Lords identified that the one possible interpretation of the clause would lead to a "windfall" – a significant financial advantage – for the appellant. Their reasons hinged significantly on their view that this was a consequence inconsistent with commercial sense, which the parties were unlikely to have intended. This article analyses the relevance of a "windfall" in the context of the modern common sense approach to the construction of contracts. It concludes that the Court’s reliance upon a "windfall" of this kind goes beyond the bounds of commercial interpretation and introduces problematic notions of substantive fairness into a business common sense approach to the interpretation of contracts.